Monitoring in Neurointensive Care – The Challenge to Detect Delayed Cerebral Ischemia in High-Grade Aneurysmal SAH - Sarrafzadeh, Asita S.; Vajkoczy, Peter; Bijlenga, Philippe; Schaller, Karl (Frontiers in Neurology, 2014)
The problem – Delayed cerebral ischemia Delayed cerebral ischemia (DCI) is a feared and significant medical complication following aneurysmal subarachnoid hemorrhage (aSAH). It occurs in about 30% of patients surviving the initial hemorrhage, mostly between days 4 and 10 after aSAH. Clinical deterioration attributable to DCI is a diagnosis of exclusion and especially difficult to diagnose in patients who are comatose or sedated. The latter are typically patients with a high grade on the World Federation of Neurosurgical Societies scale (WFNS grade 4-5), which represent approximately 40-70 % of the patient population with ruptured aneurysms. In this group of patients, the incidence of DCI is often underestimated and higher compared to low WFNS grade patients. To overcome difficulties to diagnose DCI, which is especially relevant in sedated and comatose patients, the article reports the most recent recommendation for definition of DCI and discusses their advantages and problematic issues in Neurocritical Care practice. Finally, appropriate neuromonitoring techniques and their clinical impact in high grade SAH patients are summarized.